Implikasi Kafaah terhadap Maraknya Pernikahan Dini - Muhammad Zainuddin Sunarto; Mohamad Syariful Umam (LP2M STIT Palapa Nusantara, 2023)
Marriage with teenagers under the age of 20 who are not ready to marry is known as